Design of Microstrip Antenna Single Patch Semi Circular at 2.4 GHz Frequency with Inset Feed Method - baihaqi, kirza (JITE (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING), 2019)
The use of technology using cable has now been replaced by wireless communication technology, where most users use access point devices that have a limited emission range because on omnidirectional radiation, so we need an antenna that has a directional radiation pattern for a more directed emission range. Semi circular single patch microstrip antenna with inset feed method is one that can be used for this problem. In this final project, microstrip antennas can be applied to WLAN systems. The results of the test found that the antenna can work at a frequency of 2.4570000 GHz. And besides that, also obtained a return loss of -25.68 dB, VSWR of 1.122 dB, bandwidth of 84.250000 MHz, Gain of 13.96 dBi, Average LOS (Line Of Sight) of 24.73 Mbps for uploads and 10.37 Mbps for downloads, Average NLOS (Not Light of Sight) of 14.34 Mbps for uploads and 7.78 Mbps for downloads, Distance testing along 130 meters of LOS conditions and 140 meters of Lossess conditions, the results obtained are feasible to be implemented on wifi systems and other communication systems with a 2.4 GHz frequency.